2022
DOI: 10.1039/d2sc04794b
|View full text |Cite
|
Sign up to set email alerts
|

Tandem electrocatalytic CO2 reduction with Fe-porphyrins and Cu nanocubes enhances ethylene production

Abstract: Copper-based tandem schemes have emerged as promising strategies to promote the formation of multi-carbon products of the electrocatalytic CO2 reduction reaction. In such approaches, the CO-generating component of the tandem...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…A vast library of ligand exchange protocols has been developed and tailored for a multitude of applications. For example, NC-based photovoltaics benefit from the introduction of ligands with short alkyl chains or halide ligands on the NC surface, because these ligands optimize the NC packing density and favor efficient charge transport. , Further, synergistic enhancement of heterogeneous catalysts has been attained by grafting organic species or organometallic complexes to the NC surface. Finally, NCs functionalized with polyaromatic hydrocarbon (PAH) ligands have emerged as excellent triplet exciton based sensitizers with applications in photocatalysis, , optoelelctronics, , optogenetics, , and bioimaging. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast library of ligand exchange protocols has been developed and tailored for a multitude of applications. For example, NC-based photovoltaics benefit from the introduction of ligands with short alkyl chains or halide ligands on the NC surface, because these ligands optimize the NC packing density and favor efficient charge transport. , Further, synergistic enhancement of heterogeneous catalysts has been attained by grafting organic species or organometallic complexes to the NC surface. Finally, NCs functionalized with polyaromatic hydrocarbon (PAH) ligands have emerged as excellent triplet exciton based sensitizers with applications in photocatalysis, , optoelelctronics, , optogenetics, , and bioimaging. …”
Section: Introductionmentioning
confidence: 99%
“…We selected these NCs, as they have historically benefited from being coupled to photoactive ligands. For instance, PbS, CuInS 2 , and CsPbBr 3 passivated by PAH ligands have found great use in incoherent photon conversion and photocatalyst. ,,, The coupling of PAH ligands with lanthanide-based upconverting nanoparticles (UCNPs) can drastically increase the absorption cross-section of the chromophore/NC hybrids, resulting in a significant enhancement of the upconverted emission intensity. ,, Finally, plasmonic NCs can also be coupled to chromophores, which benefits photo and electrocatalytic applications. …”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the design of tandem systems have so far focused on the coupling of Cu with a second metallic domain (Zn, 21,22 Au 23 or Ag [24][25][26][27] ) as the CO-generating catalyst. Molecular catalysts, such as cobalt phthalocyanine 28 and iron porphyrin 29,30 have also been successfully employed as the COgenerating catalyst in the context of tandem schemes. Compared to metals, molecular catalysts offer additional versatility for varying the local CO concentration and production rate thanks to the superior chemical tunability via synthetic modications of molecules versus materials.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to metals, molecular catalysts offer additional versatility for varying the local CO concentration and production rate thanks to the superior chemical tunability via synthetic modifications of molecules versus materials. 30 Despite their promise, no experimental work has investigated yet the influence of the spatial arrangement of the components on the catalytic performance of molecular-Cu based tandem systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental works also propose the tandem electrocatalyst for CO 2 RR on nanocatalysts, where the CO* forms on one type of active site and migrates to other active sites for CC coupling with lower energy barriers. [28,29] Wang et al have reported using the Ni-N-C SACs and Cu nanoparticles as the active sites for the generation of CO* and C 2 products, respectively. [30] The proposed Cu/Ni-N-C has shown high efficiency of 80% FE and a production rate of over 500 mA cm −2 for C 2 products.…”
Section: Introductionmentioning
confidence: 99%